Static Plantar Pressure Distribution Measured Using PodoPrint Aluminum Platform in Multiple Sclerosis Patients: A Case–Control Study. - Ruiz-Sánchez, Francisco Javier; Martins, María do Rosario; Losa-Iglesias, Marta Elena; Becerro-de-Bengoa-Vallejo, Ricardo; Gómez-Salgado, Juan; Saavedra‐García, Miguel Ángel; López-López, Daniel; Jiménez-Cebrián, Ana María (Wiley, 2025)
Multiple sclerosis (MS) is a complex early-onset neurological disorder with significant functional implications. Neuroinflammation and neurodegeneration are the primary pathological processes underlying MS, both of which may alter lower limb loading patterns. These alterations can be evaluated through static plantar pressure distribution. This study hypothesized that patients with MS would exhibit higher static plantar pressures compared to healthy controls.
Keywords: Podologia; Pies - Fisiología; Esclerosis múltiple; Foot